Аудит учебное пособие - Данилевский Ю. А. Юрий Александрович; Шапигузов С. М. Сергей Михайлович; Ремизов Н. А. Николай Александрович; Старовойтова Е. В. Елена Витальевна (Москва, ФБК-Пресс, 2002)
Исключено из фонда НТБ ТПУ